Answer:
D
Explanation:
The starting term is a1.
That's the very first term.
a1 = - 10
The second term = -17 which means that you added - 7 to - 10.
So d must be - 7
The formula must be
an = a1 + (n - 1)*d
an = -10 + (n - 1)(-7)
You might wonder why it is n - 1. The reason is because the first term is already added on the right side. The -1 means that we have already included the first term.
We should try the formula out to see what it does. Let's find a4
a4 = -10 + (4 -1)*-7
a4 = -10 + 3(-7)
a4 = -10 - 21
a4 = - 31 which is what the question suggests.